The Evolution of Methodical Approaches for Evaluation the Efficiency of the Activities of Scientific and Research Organizations in the Czech Republic - Zhukovych, І. A.; Yehorov, I. Yu. (Statistics of Ukraine, 2020)
The article deals with the evolution of methodological approaches used in the Czech Republic to assess the effectiveness of scientific institutions. This country shares common features with Ukraine in the organization of science and it is one of the most successful examples of socio-economic and organizational reforms in Eastern Europe. It is showed that the evaluation method, introduced in the Czech Republic since 2004, was initially purely quantitative and focused exclusively on research results such as publications, patents, prototypes, and the like. Authors conclude that the quantitative assessment did not take into account the quality of research; they also poorly reflected the importance of the results, and encouraged scientific organizations to play a dishonest game with inflating the values of individual indicators. Aggregation of all indicators into one complex indicator did not allow to evaluate the efficiency of the institution’s activities correctly, and bibliometric indicators strongly depended on the citation culture in a particular scientific discipline. The key elements of the implemented new assessment methodology (M17+) are considered, in which preference is given to the informed expert reviews, which involve a set of available indicators together with other information to make a decision on the overall assessment more comprehensive. Use M17+ will provide the following opportunities: to evaluate the results and impact of scientific activities; to make a general forecast for the development of enterprises; evaluate departmental structures and different missions of institutions under evaluation; to utilize views of the partners; evaluate the institution in the national and international contexts; provide information for the allocation of public funds secured for the institutional development of scientific institutions. The conclusion is made that the switching from the simplified, purely mechanistic approaches to assessment indicates the recognition of the complexity of scientific activities and the diversity of functions of research institutes in the socio-economic development of the state. Studying the experience of evaluating research institutions in the Czech Republic is of great importance for Ukraine as a country with European integration intentions, especially in the context of limited funding for science and increased difficulties with obtaining the budget money.